"What Is This Asking From Me?" An Extended Review of The Rediscovery of Teaching by Gert J. J. Biesta. (2nd January 2020) - Dijkman, Beatrijs
Abstract: This essay is a reflection on The Rediscovery of Teaching by Gert Biesta. The author explores how freedom and subjectivity are central to understanding Biesta's work on existential aspects of education. She gives an example from her own practice that demonstrates the interruption of the educational discourse brought about by changing arrangements for assignment and assessment in adult training. The case study indicates that education is not about setting objective goals but rather about ways to become "a self " for the one who teaches and the one who is taught.